2015
DOI: 10.1073/pnas.1513432112
|View full text |Cite
|
Sign up to set email alerts
|

5-hydroxymethylation of the EBV genome regulates the latent to lytic switch

Abstract: Latent Epstein-Barr virus (EBV) infection and cellular hypermethylation are hallmarks of undifferentiated nasopharyngeal carcinoma (NPC). However, EBV infection of normal oral epithelial cells is confined to differentiated cells and is lytic. Here we demonstrate that the EBV genome can become 5-hydroxymethylated and that this DNA modification affects EBV lytic reactivation. We show that global 5-hydroxymethylcytosine (5hmC)-modified DNA accumulates during normal epithelial-cell differentiation, whereas EBV+ NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 49 publications
(85 reference statements)
1
38
0
Order By: Relevance
“…Importantly, TET2 loss has recently been implicated in the development of EBV ϩ nasopharyngeal carcinoma (NPC) (47). EBV exclusively, lytically infects more differentiated normal epithelial cells (48)(49)(50)(51)(52)(53), and thus, the viral genome remains highly unmethylated (11).…”
Section: Tet2 Promotes Ebv Type III Latency Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, TET2 loss has recently been implicated in the development of EBV ϩ nasopharyngeal carcinoma (NPC) (47). EBV exclusively, lytically infects more differentiated normal epithelial cells (48)(49)(50)(51)(52)(53), and thus, the viral genome remains highly unmethylated (11).…”
Section: Tet2 Promotes Ebv Type III Latency Gene Expressionmentioning
confidence: 99%
“…However, in the case of NPC, EBV maintains a latent infection and the viral genome becomes highly methylated (54). We recently showed that TET2 5hmC modifies the EBV genome to promote lytic gene expression in epithelial cells and that NPC tumors lose TET2 expression, which may enhance oncogenesis (47). Furthermore, TET2 was recently found to be a resistance factor of EBV-induced DNA methylation in gastric carcinoma cells, demonstrating that TET2 may have an important role in protection against EBV ϩ tumor development (55).…”
Section: Tet2 Promotes Ebv Type III Latency Gene Expressionmentioning
confidence: 99%
“…In 293T cells stably infected with an EBV genome, high occupancies of Zta were observed in methylated promoters of BALF2, BMRF1, Rta, and BHLF1, whereas these bindings were disrupted once the EBV genome is hypomethylated (54). In addition, during the early stages of the lytic cycle in IgG-induced EBV-positive Akata cells, Zta associated with the promoters of BKRF4, BLLF2, and BRRF1.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that a methylated EBV genome is essential for viral lytic reproduction (51,53,72), as the immediate-early protein Zta preferentially binds to methylated viral promoters (54,(73)(74)(75). In 293T cells stably infected with an EBV genome, high occupancies of Zta were observed in methylated promoters of BALF2, BMRF1, Rta, and BHLF1, whereas these bindings were disrupted once the EBV genome is hypomethylated (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation